2019
DOI: 10.1093/femsle/fnz150
|View full text |Cite
|
Sign up to set email alerts
|

Test parameters and cell chain length of Streptococcus thermophilus affect the microbial adhesion to hydrocarbons assay: a methodical approach

Abstract: The microbial adhesion to hydrocarbons (MATH) test is one of the most common method to determine the hydrophobicity of cell surfaces. Despite its prevalence, no standard test parameters are used in literature, making a direct comparison of data almost impossible. Criticism also focuses on test parameters that may mask hydrophobic interactions and hence lead to erroneous test results. We methodically investigated the impact of different MATH test parameters on the calculation of the cell surface hydrophobicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Despite of these methods being widely used, several authors have chosen bacterial adhesion to hydrocarbons to be one of the simplest methods to evaluate microbial hydrophobic features (Nachtigall et al . 2019). In the present study, we tested the ability of 54 tomato epiphytic LAB to attach to a liquid and solid hydrophobic material such as hexadecane and polystyrene, respectively, in order to identify hydrophobic strains with potential affinity to tomato surface.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of these methods being widely used, several authors have chosen bacterial adhesion to hydrocarbons to be one of the simplest methods to evaluate microbial hydrophobic features (Nachtigall et al . 2019). In the present study, we tested the ability of 54 tomato epiphytic LAB to attach to a liquid and solid hydrophobic material such as hexadecane and polystyrene, respectively, in order to identify hydrophobic strains with potential affinity to tomato surface.…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall hydrophobicity measurements were performed as described by Kos et al [ 73 ] and Nachtigall et al [ 74 ]. The adherence was calculated from the following equation, (1 − A t )/A 0 × 100, where A t means the absorbance at time 15 min and A 0 the absorbance at time 0.…”
Section: Methodsmentioning
confidence: 99%
“…The microbial adhesion to hydrocarbons (MATH) method is the most common method for hydrophobicity determination. However, the direct comparison of data obtained using this method is difficult because numerous parameters can influence the final hydrophobicity values [23]. The overall adhesion is a complex process involving multiple further parameters; for example, surface EPS, S-layer protein, and lipoteichoic acid [46].…”
Section: Effects Of S Thermophillus Ccdm 144 and E Faecium Ccdm 922a Selenization On Cell Surface Hydrophobicitymentioning
confidence: 99%
“…Some EPS can also have beneficial effects on digestion as they remain for an extended period in the digestive tract and thus provide suitable conditions for the colonization of mucous membranes by probiotic bacteria [48]. In particular, EPS production may be related to hydrophobicity and cell surface properties as a portion of the EPS can be liberated into the medium whereas capsular EPS remains bound to the cell wall of the microorganisms, which may affect cell surface properties [23]. Notably, both of the strains tested were EPS producers and we had previously confirmed that both strains were positive for the presence of eps genes encoding EPS; we also confirmed the phenotypic expression of EPS production in the form of increased viscosity of the products fermented by these strains.…”
Section: Effects Of S Thermophillus Ccdm 144 and E Faecium Ccdm 922a Selenization On Cell Surface Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation